Case series: Intraoperative neuromonitoring and angiography in the surgical treatment of vascular malformations - Šmigoc, Tomaž; Kozorog, Ninna; Ravnik, Janez (Frontiers in Neurology, 2023)
In surgical treatment of cerebral vascular malformations, e.g. aneurysm, arteriovenous malformations, the risk of ischemic complications is 6.7% and a residual aneurysm is possible in 5.2% of these cases. Ischemic lesions can result in permanent neurological deficit, and a residual aneurysm can lead to the recurrence of the aneurysm in 2% of cases.In this article we present five cases (two cases of ruptured aneurysms, two cases of non-ruptured aneurysms and a case of arteriovenous malformation) in which we reduced the before-mentioned risks with the use of intraoperative neuromonitoring and angiography. Intraoperative neuromonitoring (IONM) is used to measure motor and sensory evoked potentials to detect brain hypoperfusion. Intraoperative angiography with the dye indocyanine green (ICG-A), which fluoresces in a vessel under a microscope after intravenous administration, helps to identify residual aneurysm sac and distal blood flow. With the use of IONM and ICG-A we identified abnormalities and adjusted our interventions and treatment. IONM and ICG-A can lead to better outcome after surgical treatment of cerebral vascular abnormalities.